PELATIHAN PEMASARAN ONLINE PADA USAHA SANGKAR BURUNG ‘BERKAH SANGKAR' - Ibnu Reza Anugrah; Sarah Dien Hawa; Gilang Utomo; Gagas Rizal Pribadi; Didi Yogi Prawiro (Kanigara, 2023)
The purpose of this service is to increase sales of bird cages andexpand marketing to businesses (Berkah Sangkar) by introducing them toonline marketing through social media which now makes the process easiersale.This Berkah Cage business is located in Kalisalak Hamlet, KarangbawangVillage, District Ajibarang, Banyumas Regency. The method used in this service is methodBINTEK (Technological Guidance) training and mentoring. Through the perpetrator's method Businesses can improvetheir sales process and increase revenue.